2021
DOI: 10.3390/en14144109
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning of Steel Producers to the Steelworks 4.0—Literature Review with Case Studies

Abstract: The publication presents a picture of modern steelworks that is evolving from steelworks 3.0 to steelworks 4.0. The paper was created on the basis of secondary sources of information (desk research). The entire publication concerns the emerging opportunities for the development of the steel producers to Industry 4.0 and the changes already implemented in the steel plants. The collected information shows the support environment for changes in the steel sector (EU programs), the levels of evolution of steel mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Here's what they found [31,32]: − the beginning of the intensive digitization of the steel industry in the world begins in the 1990s, in Poland it begins at the beginning of the second decade of this century, the Polish steel industry is gradually implementing digital technologies in production processes (the increasing polarization of the Industry 4.0 concept makes it easier for steel mills to implement high technologies), there are segmental (in various areas of activity) investment projects for digital technologies (cases studies: ArcelorMittal, Thyssenkrupp, Tata Steel Group), − digital technologies in steel mills monitor the work of selected production sections and/or support basic technological devices (control parameters, control the operation of machines) the largest (key) processes and technologies, e.g. a blast furnace is supervised and controlled using IT systems, devices in steel plants and in rolling mills are equipped with sensors that provide data on the course of the process and facilitate their control, technologies with sensors create production networks, e.g.…”
Section: Key Directions For Industry 40 In the Steel Sec-tor Transfor...mentioning
confidence: 74%
See 1 more Smart Citation
“…Here's what they found [31,32]: − the beginning of the intensive digitization of the steel industry in the world begins in the 1990s, in Poland it begins at the beginning of the second decade of this century, the Polish steel industry is gradually implementing digital technologies in production processes (the increasing polarization of the Industry 4.0 concept makes it easier for steel mills to implement high technologies), there are segmental (in various areas of activity) investment projects for digital technologies (cases studies: ArcelorMittal, Thyssenkrupp, Tata Steel Group), − digital technologies in steel mills monitor the work of selected production sections and/or support basic technological devices (control parameters, control the operation of machines) the largest (key) processes and technologies, e.g. a blast furnace is supervised and controlled using IT systems, devices in steel plants and in rolling mills are equipped with sensors that provide data on the course of the process and facilitate their control, technologies with sensors create production networks, e.g.…”
Section: Key Directions For Industry 40 In the Steel Sec-tor Transfor...mentioning
confidence: 74%
“…From the beginning of the 90s, intensive projects of digitization of the steel industry were implemented in many countries around the world. Gajdzik and Wolniak [31,32] in their papers presented cases studies about digitalization in steel industry.…”
Section: Key Directions For Industry 40 In the Steel Sec-tor Transfor...mentioning
confidence: 99%
“…The novelty of the concept in this study comes from the application of an advanced mathematical apparatus for the purposes of product quality analysis. However, practical applications of this method will not be possible before the Fourth Industrial Revolution because of the insufficient level of digitization of manufacturing processes [66,67]. Only after the emergence of Industry 4.0 and Quality 4.0 with the accompanying phenomena will the application of this kind of mathematically advanced method be possible in business practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that this method could be a contribution towards the transformation of the baking industry, towards Industry 4.0. In Industry 4.0, we digitalize all data, and analyze them using big data or artificial intelligence methods [65][66][67][68]. It is concluded that this method based on real data from bakeries will speed up the implementation of Industry 4.0 therein.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the European context [42], digitization as the core of the Industry 4.0 concept [47,48] is much more than just automation development [44,49]. Digital transformation is business transformation enabled by digitalization [12,50]. Digitalization is "a multidimensional process that leads to the convergence of the real and virtual worlds, becoming the main driver of innovation and change in the economy" [49].…”
Section: Literature Review 21 Definitional Issuesmentioning
confidence: 99%